2008
DOI: 10.1017/s0007114507842826
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and its determinants in adolescents from the Northern Ireland Young Hearts 2000 cohort

Abstract: Despite recent concerns about the high prevalence of sub-clinical vitamin D deficiency in adolescents, relatively few studies have investigated the underlying reasons. The objective of the present study was to investigate the prevalence and predictors of vitamin D inadequacy among a large representative sample of adolescents living in Northern Ireland (54-558N). Serum concentrations of 25-hydroxyvitamin D (25(OH)D) were analysed by enzyme-immunoassay in a subgroup of 1015 of the Northern Ireland Young Hearts 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
71
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 39 publications
20
71
3
Order By: Relevance
“…Fitness may also be associated with vitamin D concentrations because greater fitness is likely linked to increased outdoor activities (38) and thus exposure to sunlight (6) , as predicted in the present study. It should however also be mentioned that girls (12-14 years) with low s-25(OH)D have been shown to generate less power, jump less height and have lower velocity than girls with higher s-25(OH)D concentrations, measured as the 'Esslinger Fitness Index' which represents efficiency and asymmetry of movement and maximum voluntary force of each leg (39) , suggesting that a lower CRF as a consequence of lower 25(OH)D could be one potential explanation for the positive association between CRF and 25(OH)D. Several studies worldwide have reported higher vitamin D status in boys compared with girls, although the reason is unclear (6)(7)(8) , but these studies were only examining vitamin D status, irrespective of intake. In the present study boys had higher fitness and higher intakes of vitamin D than girls, but there was no gender difference in serum vitamin D status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fitness may also be associated with vitamin D concentrations because greater fitness is likely linked to increased outdoor activities (38) and thus exposure to sunlight (6) , as predicted in the present study. It should however also be mentioned that girls (12-14 years) with low s-25(OH)D have been shown to generate less power, jump less height and have lower velocity than girls with higher s-25(OH)D concentrations, measured as the 'Esslinger Fitness Index' which represents efficiency and asymmetry of movement and maximum voluntary force of each leg (39) , suggesting that a lower CRF as a consequence of lower 25(OH)D could be one potential explanation for the positive association between CRF and 25(OH)D. Several studies worldwide have reported higher vitamin D status in boys compared with girls, although the reason is unclear (6)(7)(8) , but these studies were only examining vitamin D status, irrespective of intake. In the present study boys had higher fitness and higher intakes of vitamin D than girls, but there was no gender difference in serum vitamin D status.…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated that s-25(OH)D levels are up to 24 % lower during winter compared with summer and they are inversely correlated with parathyroid hormone (PTH) levels in 14-year-old children, but the association between s-25(OH)D and PTH seems to be dependent on age, increasing with increasing age (14) . Higher s-25(OH)D concentrations have been reported in boys compared with girls both during childhood and adolescence (1-21 years), although the reason is unclear (6)(7)(8) . The influence of physical activity or fitness as a predictor of vitamin D status in children is virtually unknown.…”
Section: -Hydroxyvitamin D (S-25(oh)d)mentioning
confidence: 98%
See 1 more Smart Citation
“…(13) Serum 25(OH)D levels are considered the best marker of vitamin D status and have been used commonly to assess the prevalence of vitamin D deficiency/insufficiency in healthy children and adolescents. (9,10,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) However, a clear understanding of the biologic significance of given concentrations of circulating 25(OH)D is still lacking, and reference ranges for vitamin D are being reassessed on the basis of what constitutes a normal concentration compared with optimal concentrations. (27)(28)(29) Most clinicians agree that serum 25(OH)D levels below 25 to 30 nmol/L (10 to 12 ng/mL) may lead to nutritional rickets, hypocalcemic convulsions, dental problems, and poor growth in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…(27)(28)(29) Most clinicians agree that serum 25(OH)D levels below 25 to 30 nmol/L (10 to 12 ng/mL) may lead to nutritional rickets, hypocalcemic convulsions, dental problems, and poor growth in children and adolescents. (30)(31)(32)(33)(34)(35)(36) But the lower threshold of optimal vitamin D status for bone health and calcium homeostasis during growth is still under discussion, with cutoff values proposed from 25 to 30 to 70 to 90 nmol/L in children, (9,10,23,36) as in adults. (12) Differences in the 25(OH)D assays used might explain some discrepancies, especially because results have not been validated systematically using external control assessment schemes.…”
Section: Introductionmentioning
confidence: 99%